Reactivation of Denervated Schwann Cells by Embryonic Spinal Cord Neurons to Promote Axon Regeneration and Remyelination - Xinyu Fang; Chaofan Zhang; Chongjing Zhang; Yuanqing Cai; Zibo Yu; Zida Huang; Wenbo Li; Wenming Zhang (Stem Cells International)
In peripheral nerve injuries (PNIs) in which proximal axons do not regenerate quickly enough, significant chronic degeneration of Schwann cells (SCs) can occur at the distal stump of the injured nerve and obstruct regeneration. Cell transplantation can delay the degeneration of SCs, but transplanted cells fail to generate voluntary electrical impulses without downstream signal stimulation from the central nervous system. In this study, we combined cell transplantation and nerve transfer strategies to investigate whether the transplantation of embryonic spinal cord cells could benefit the microenvironment of the distal stump of the injured nerve. The experiment consisted of two stages. In the first-stage surgery, common peroneal nerves were transected, and embryonic day 14 (E14) cells or cell culture medium was transplanted into the distal stump of the CPs. Six months after the first-stage surgery, the transplanted cells were removed, and the nerve segment distal to the transplanted site was used to bridge freshly cut tibial nerves to detect whether the cell-treated graft promoted axon growth. The phenotypic changes and the neurotrophic factor expression pattern of SCs distal to the transplanted site were detected at several time points after cell transplantation and excision. The results showed that at different times after transplantation, the cells could survive and generate neurons. Thus, the neurons play the role of proximal axons to prevent chronic degeneration and fibrosis of SCs. After excision of the transplanted cells, the SCs returned to their dedifferentiated phenotype and upregulated growth-associated gene expression. The ability of SCs to be activated again allowed a favorable microenvironment to be created and enhanced the regeneration and remyelination of proximal axons. Muscle reinnervation was also elevated. This transplantation strategy could provide a treatment option for complex neurological injuries in the clinic.